Income diversification and household welfare in Uganda 1992–2012 - Khan, Rumman; Morrissey, Oliver (Elsevier Ltd, 2023)
Abstract •Non-agricultural diversification is welfare improving for rural households.•Agricultural wage labour associated with lower welfare for rural females.•Access to farm income improves welfare of female headed urban households.•Off-farm specialisation is more beneficial for male headed urban households.•Remittances only raised welfare in the 2000s when prevalence was declining. We use five waves of household surveys in Uganda, from 1992/3 to 2011/12, to study income diversification and its effect on the welfare of rural and urban households during a period of sustained economic growth and poverty reduction, comparing the 1990s to the 2000s, and disaggregating by gender of the household head. Diversification is measured in terms of access to incomes from agriculture (farming), agricultural wage, self-employment (informal), wage employment and remittances. The analysis shows substantial and evolving variation in the effects of diversification across rural/urban locations and gender of the household head. Diversification became increasingly beneficial for welfare over time in rural areas, particularly for male headed households, but not for female headed households that diversified into agricultural wage employment. Diversification was also important for the livelihoods of urban households, but with large differences across male and female headed households likely reflecting differentials in the returns to non-agricultural employment. Remittances were associated with increasing welfare in the 2000s for all households, although the proportion of households receiving remittances has been declining.
Keywords: Non-agricultural diversification; Uganda; Diversification; incomes ; household